2020
DOI: 10.3390/pathogens9060477
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Parasitic Helminths in the Small Intestine of the Red Fox (Vulpes vulpes)

Abstract: The aim of the study was to analyze the distribution of the main groups of parasitic helminths within the small intestine of the red fox on the example of animals coming from eastern Poland. Two hundred and sixteen red foxes shot in eastern Poland were used in the investigation. Before examination, each small intestine was divided into three equal parts: anterior (A), middle (M), and posterior (P). Each part was examined separately with the sedimentation and counting technique. Six different types of intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
2
7
0
5
Order By: Relevance
“…However, it is difficult to draw conclusions from these comparisons because the species/genotypes were not identified in the studies. In our study, most of the tapeworms were found in the anterior part of the small intestine; this is consistent with the description of E. granulosus, which, unlike E. multilocularis, is more predisposed to the anterior and middle part of the intestine [40][41][42].…”
Section: Discussionsupporting
confidence: 92%
“…However, it is difficult to draw conclusions from these comparisons because the species/genotypes were not identified in the studies. In our study, most of the tapeworms were found in the anterior part of the small intestine; this is consistent with the description of E. granulosus, which, unlike E. multilocularis, is more predisposed to the anterior and middle part of the intestine [40][41][42].…”
Section: Discussionsupporting
confidence: 92%
“…Next, they are swallowed and develop in the small intestine, reaching 3–6 mm in length and 1–2 mm in breadth as adult flukes [ 32 ]. In studies on the distribution of the parasites in the small intestines of foxes, A. alata were detected mostly in the anterior parts of the intestines in almost all infected foxes (99.4%) [ 35 ]. Eggs (oval, size 98–125 × 62–81, light brown and operculated with a lid–operculum), which are a dispersive form of the parasite, are laid in definitive hosts and excreted with the feces into the environment.…”
Section: Life Cycle Of a Alatamentioning
confidence: 99%
“…In Poland, the southern provinces presented a comparable calculated prevalence to Austria (6.8–7.7% for Małopolskie, Śląskie and Opolskie); the western provinces presented a similar prevalence to Germany (10.9% for Dolnośląskie and 14.1 for Opolskie); and the north-eastern provinces presented the highest prevalence in Poland, which is comparable to the prevalence in Latvia in some cases (for example, 43.3% in Warmińsko-Mazurskie province and 43.9% in Latvia). This trend is also visible among definitive hosts: the positive rates in red foxes were 78.7% in Poland and 94.8% in Lithuania ( Bružinskaitė-Schmidhalter et al, 2012 ; Karamon et al, 2020 ), compared to 4.7% and 5.3% in Croatia and Italy, respectively ( Rajković-Janje et al, 2002 ; Fiocchi et al, 2016 ). This trend is probably connected with the fact that northern countries offer generally better conditions for the complete cycle of A. alata , i.e., higher levels of wetland cover ( Schleupner 2007 ).…”
Section: Discussionmentioning
confidence: 81%
“…These species are present as definitive hosts in the A. alata cycle ( Takeuchi-Storm et al, 2015 ; Korpysa-Dzirba et al, 2021 ), and the red fox is considered to be the main definitive host of A. alaria in Europe ( Portier et al, 2011 ). Indeed, a recent study in Poland found a high prevalence of A. alata in red foxes (78.7%) based on intestinal examination ( Karamon et al, 2020 ). A. alata does not yet appear have been described in raccoon dogs in Poland; however, it has been confirmed in neighboring Lithuania, and the data suggests that A. alata may even be found in greater abundances in raccoon dogs than in red foxes ( Bružinskaitė-Schmidhalter et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%